Improving Spatial Resolution of SMAP Surface Soil Moisture through the Synergy of Radar-Microwave Observations at the Firoozabad Watershed, Ardabil - Ayoob Karami; Hamid Reza Moradi; Ali Jafar Mousivand (پژوهش‌های آبخیزداری, 2020)
Surface soil moisture retrieval using microwave remote sensing, as the most promising method, has been highly valued due to its great accuracy and temporal resolution in broad scales. However, its coarse resolution limits regional scale applications. This study aims to apply the optional downscaling algorithm to generate high resolution soil moisture (θf) over Firoozabad Watershed, Ardabil, Iran. The algorithm integrates the advantage of Sentinel-1 (S-1) radar and the SMAP Radiometer soil moisture to make a linear correlation between the satellite soil moisture (θc) and the radar backscatter (σo) at each coarse pixel. The outputs were compared with the soil moisture measurements collected from individual points in the study area. The values of 0.043 cm3/cm3 and 0.039 cm3/cm3, respectively, were obtained for RMSE and UnbRMSE at 1 km resolution. This result are close to the SMAP’s downscaled target accuracy (RMSE = 0.05, cm3/cm3). Taken together, point measurement has limitations in terms of spatial representation and spatial extent, especially in a watershed scale data analysis; therefore, utilizing the freely available SMAP soil moisture data and its downscaled version with the S-1 SAR data could be considered as an efficient and low cost tool to be used in research and implementation for the local and regional applications.